Alteration of the isoenzymes patterns in corn seeds infected by fungi - Silva, Edvaldo Aparecido Amaral da; Pinho, Édila Vilela de Resende Von; Vieira, Maria das Graças Guimarães Carvalho; Carvalho, Maria Laene Moreira de; Machado, José da Cruz (Pesquisa Agropecuaria Brasileira, 2000)
This work aimed at studying the interference of the fungi Aspergillus flavus, Fusarium moniliforme and Penicillium spp. on the electrophoretic patterns of corn seeds. Normally, these patterns are used in the identification of cultivars and certification of genetic purity of this species. Seeds of the cultivar C-805 were artificially inoculated with the referred fungi; part was treated with Benomyl and Thiabendazole and part was untreated. All seed samples were stored in growing chamber incubator at 25 °C and 95% of relative humidity for 30 days. In the electrophoretic analysis, a seed sample was also evaluated which had not been kept in growing chamber incubator, in order to detect possible interferences of the growing chamber environment on the electrophoretic patterns. The results allowed to conclude that the seed infection by the Aspergillus flavus, Fusarium moniliforme and Penicillium spp. fungi promotes alterations in the electrophoretic patterns of the malate-dehydrogenase, esterase, acid phosphatase, peroxidase and glutamate-oxalacetate-transaminase isoenzymes. Infection by Aspergillus flavus caused considerable alteration in both intensity and number of bands of the isoenzymatic patterns of alcohol-dehydrogenase and malate-dehydrogenase.